PENGARUH INTERNET FINANCIAL REPORTING DAN TINGKAT PENGUNGKAPAN INFORMASI WEBSITE TERHADAP FREKUENSI PERDAGANGAN SAHAM PERUSAHAAN (Studi pada Perusahaan yang Terdaftar di Indeks LQ45 Bursa Efek Indonesia) - Priyo Sigit Budi Santiko (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
With the development of information technology is very fast, the internet has become an effective tool in the delivery of information particularly in the business sector. Internet Financial Reporting is voluntary disclosure form that made the company to provide all financial information of the company through the internet. This will have an impact over the long term for the company because the stakeholders have the right to obtain information about any company's activity that will affect their decisions. Disclosure of information via the internet is also the company's efforts to reduce the asymmetry of information by outside parties. It is also a form of corporate communications with outside parties to improve their confidence and reduce uncertainty will be the prospect of a company that will come. This research aims to know the influence of the Internet Financial Reporting and the level of disclosure of information Website Of the frequency of stock trading in Company Securities Indonesia LQ45 Index. The type of research used in this research is explanatory research (research description) that aims to explain the causal relationship between the causal variables through hypothesis testing. The Data collected through the study documentation on the Indonesia Stock Exchange Fact 2013. To test the hypothesis presented in this study used multiple regression analysis. The results of this research show that the negative effect and not IFR significantly to frequency of trading stocks. This indicates that there is no practice IFR or does not affect the level of frequency of stock trading. While the level of disclosure of a positive and influential website significantly to trade company stock LQ45 frequency. So the higher the level of disclosure of the high-frequency stock trading. Keyword : Internet Financial Reporting, The level of the disclosure of information website¸ the frequency of stock trading